2019
DOI: 10.1080/01425692.2018.1489219
|View full text |Cite
|
Sign up to set email alerts
|

Equality of opportunity for work experience? Computing students at two UK universities “play the game”

Abstract: A recent UK Government commissioned study found concerning levels of unemployment among computing students from disadvantaged, black and minority ethnic backgrounds. The study highlighted that work experience was a factor in increased levels of graduate employment. As such, it is vital that students have equal access to such work experience. This study considers the availability of work experience to 140 computing students at two city centre UK universities. Data analysis considered socioeconomic background an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This situation rises concerns regarding equal access of students to internship opportunities and strategies to ensure this. Recent research has been claiming that internships are replicating social inequalities [51,52]. As such, institutional investments in monitoring and evaluating these strategies are crucial to grant equal access of students to internships and guarantee the quality of the learning experiences, as envisaged by the Agenda 2030 (Goal 4).…”
Section: Discussion: Framing the 'Lunar Side' Of Curricular Internshimentioning
confidence: 99%
See 1 more Smart Citation
“…This situation rises concerns regarding equal access of students to internship opportunities and strategies to ensure this. Recent research has been claiming that internships are replicating social inequalities [51,52]. As such, institutional investments in monitoring and evaluating these strategies are crucial to grant equal access of students to internships and guarantee the quality of the learning experiences, as envisaged by the Agenda 2030 (Goal 4).…”
Section: Discussion: Framing the 'Lunar Side' Of Curricular Internshimentioning
confidence: 99%
“…It is believed that these moments of participatory reflection should be done on a regular basis, since roles and persons change over time (a supervisor is not only a supervisor in the university, and a student is not only an intern during his/her internships, as he/she will be a future employee and perhaps a future employer) [50]. Internship management needs to be thought of in a long term perspective in order to maximize its sustainability and impact [52].…”
Section: Discussion: Framing the 'Lunar Side' Of Curricular Internshimentioning
confidence: 99%
“…In the study by Bathmaker et al, middle class students enjoyed advantages including recognising the opportunity for work experience, social capital to acquire access to work experience, finance as an enabler for unpaid work, and cultural capital recognised by employers. Smith et al (2019) found evidence that while a wide range of students recognised the opportunity posed by work experience, white students had more success in their applications than those from other ethnic groups.…”
Section: Social Mobility and Educationmentioning
confidence: 99%
“…Placements have been found to help students gain graduate work more quickly and start on higher salaries (Smith et al 2018b;Wilton 2012). There is evidence, however, that not all students have equal recognition of, or access to, student work placements (Bathmaker, Ingram, and Waller 2013;Smith et al 2019). In the study by Bathmaker et al, middle class students enjoyed advantages including recognising the opportunity for work experience, social capital to acquire access to work experience, finance as an enabler for unpaid work, and cultural capital recognised by employers.…”
Section: Social Mobility and Educationmentioning
confidence: 99%
“…However, the apprentices' conceptualisation of the school's on-campus students tends towards caricature, rather than representation, neglecting the proportions of our students that are older (e.g. 23% over 25) and the prevalence of work experience [27].…”
Section: Outcomes Future Work and Challengesmentioning
confidence: 99%